Individual fracture risk and the cost-effectiveness of bisphosphonates in patients using oral glucocorticoids. - van Staa, T; Geusens, P; Zhang, B; Leufkens, H; Boonen, A; Cooper, C (2007)
OBJECTIVES: There are few data on the cost-effectiveness of bisphosphonates with oral glucocorticoids (GCs). An individual patient-based pharmaco-economic model was developed. METHODS: Data were obtained from a cohort of oral GC users aged 40+ (n = 190 000) in the UK General Practice Research Database. Individualized fracture and mortality risks were calculated specific for age, sex, daily and cumulative GC dose, indication and other clinical risk factors. UK costs of medication and direct costs of fracture were obtained from National Institute for Clinical Excellence and used to estimate costs per quality-adjusted life-year (QALY) gained and fracture prevented for bisphosphonates in patients treated for 5 yrs with GCs. RESULTS: With the use of 5 mg GCs daily, the cost per one QALY gained with bisphosphonates was 41k UK pounds (95% confidence intervals 22-72k) in women aged <60 [men 40k pounds (29-54k)], 17k pounds (13-24k) in women aged 60-79 [men 43k pounds (31-60k)], 5k pounds(3-6k) in women aged 80+ [men 35k pounds (25-46k)]. With 15 mg GC, these figures were 17k pounds (14-21k), 13k pounds (10-16k) and 15k pounds (9-26k) in women and 22k pounds (17-26k), 34 pounds (23-53k) and 33k pounds (27-42k) in men, respectively. When stratifying by overall fracture risk and life expectancy at the start of GC therapy, cost per QALY increased with decreasing life expectancy. Patients with rheumatoid arthritis had comparatively better cost-effectiveness, given higher fracture risk and better life expectancy. CONCLUSIONS: The cost-effectiveness of bisphosphonates varied substantially. Bisphosphonates can be considered cost-effective in patients with higher fracture risks, such as elderly patients (with a life expectancy over 5 yrs), and younger patients with a fracture history, low body mass index, rheumatoid arthritis or using high GC doses.